Rethinking São Paulo’s Higher Education System - Marcovitch, Jacques (International Higher Education, 2022)
COVID-19 unlocked and accelerated five distinct crises in Brazil: health-related, economic, social, political, and geopolitical. In its aftermath, universities in Brazil and beyond must confront challenges related to autonomy, financing, their connection to society, and governance. Looking at public higher education in the state of São Paulo, we posit that universities must rethink their relationship to society in order to contribute to social and economic recovery.